Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.

A Landscape of Memories through the Music of Hope Lee - Feliz, Juro Kim (Nomadic Sound Worlds, 2018)
Produced by Juro Kim Feliz under the Canadian Music Centre Library Residency, Nomadic Sound Worlds is a four-part blog/podcast series exploring Canadian contemporary music through the lens of present-day global migration. A collection of essays named Letters of Transit: Reflections on Exile, Identity, Language, and Loss (ed. André Aciman, 1999) informs and inspires this project, with trajectories branching out from related themes including mobility, displacement, loss, reconciliation of polarized truths, and invention of selves. In this regard, the series will feature selected immigrant Canadian composers whose musical worlds collide with various personal stories of immigration.

Ana Sokolović. Robots musicaux et kolo serbe - Harman, Brian (La création musicale au Québec, 2018)

Their Own Agenda: The History, Development, and Culture of Women's Orchestras Outside the United States - Alger, Bonnie Eve (Université du Maryland, 2018)
Women have been active as performers of instrumental music since the Medieval period, and yet their contributions are often overlooked. This dissertation examines the history of women’s orchestras outside the United States, and explores their development, as well as reasons for existing. Several factors regarding their development are taken into consideration, including time period, country, and culture in which the ensemble is present. The birth of the women’s orchestra is traced from the ospedali of the 18th century Venice to today. All-female ensembles from England, Canada, Cuba, and Afghanistan are profiled, as well as the Women’s Orchestra in Auschwitz. Two modern-day women’s orchestras – the Allegra Chamber Orchestra in Vancouver, British Columbia, and my recital orchestra at the University of Maryland – were surveyed in an attempt to learn more about the culture of women’s orchestras. This paper seeks to answer the questions “What is the culture of women's orchestras today, and should they continue to exist?”

Aller à la quête de l’œuvre : Véronique Lacroix et les 30 ans de l’ECM+ - Champagne, Éric (Circuit : musiques contemporaines, 2018)

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Isabelle Panneton. De la rigueur à la liberté de création - Nattiez, Jean-Jacques (La création musicale au Québec, 2018)

L’apport de Maryvonne Kendergi à la SMCQ - Bail, Louise (Circuit : musiques contemporaines, 2017)
To measure Maryvonne Kendergi’s contributions to the smcq, it is necessary to revisit her career in Quebec, which was based on the solid academic and professional training she received at Parisian institutions from 1929 to 1952. Thereafter, in Montreal, she was hired by Radio-Canada for her exceptional voice, and in September 1956, she embarked on a brilliant radio career as a promoter of contemporary music. Kendergi gradually introduced the listening public to the arcana of the Montreal avant-garde. In this endeavour she was encouraged by Stockhausen’s arrival in Montreal in 1958, by composers’ efforts in organizing International Music Week in 1961, by the foundation of the smcq in 1966, and by the influence of the latter organization, particularly in its collaboration with the Université de Montréal in establishing the Musialogues in 1969. The role of Kendergi’s exceptional skills in broadening the influence of the smcq is explored in this article.
Keywords: Maryvonne Kendergi; Musialogues; Société de musique contemporaine du Québec (smcq); animatrice; host; music journalist; musicographe de radio

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article analyse la nouvelle collaboration entre la compositrice et pionnière de musique électronique, Éliane Radigue, et le Quatuor Bozzini. Débutant vers la fin des années 1960, la carrière d’Éliane Radigue se caractérise par de très longues oeuvres de musique électronique qui semblent de prime abord ne pas changer, et dans lesquelles les micro-oscillations naturelles entre les hauteurs remplacent la rythmique traditionnelle. Depuis 2001, Radigue ne travaille plus qu’avec des instrumentistes et utilise un « processus de composition intuitif » semblable à la « transmission orale de musiques traditionnelles anciennes » (Sonami 2017). Alors que les quelques intellectuels qui ont fait montre d’intérêt envers la musique de Radigue ont concentré leur attention sur l’aspect oral de ses compositions, cet article cherche ici à amener l’analyse au-delà des paramètres formels « non-écrits » de sa musique afin d’explorer comment la sonorité d’une pièce de Radigue génère de nouvelles manières de concevoir la performance et la composition. Les notes d’observation de l’auteure, la correspondance entre l’auteure, la compositrice et le quatuor, et les enregistrements des rencontres entre les Bozzini et Radigue seront utilisés pour retracer les moments de grande réaction émotionnelle causés par la sonorité très particulière que demande la musique de Radigue. Ces réactions affectives du côté de Radigue et du quatuor révèlent des points de tension entre différentes conceptions de la création collective, et réorientent complètement ce que cela signifie que de posséder, transmettre, interpréter et composer de la musique. Des spectrogrammes et des enregistrements des tentatives entreprises par les Bozzini seront utilisés dans l’étude de ces points de tension, et démontreront qu’afin de pouvoir jouer avec succès une pièce instrumentale de Radigue, les Bozzini doivent reproduire chaque élément des pièces électroniques de la compositrice; le quatuor à cordes doit se « transformer » en un étrange instrument.

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

A performer's perspective on three works for pianist and moving images : analysis with performance and practice strategies for Michel van der Aa's 'Transit', Nicole Lizée's 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby - Morano, Christopher (Université de Colombie-Britannique, 2017)
Interest in audio-visual works of art that are performed by a live pianist while integrating projected moving visual images has waxed and waned over a period of almost 300 years. The past twenty years or so has seen a re-emergence of this genre of classical music composition which places extra demands on the pianist performing these works. This dissertation explores the history of this genre, proposes a framework for analysis of these pieces, and examines from both analytical and performance perspectives three contrasting works for this medium: Michel van der Aa’s 'Transit', Nicole Lizée’s 'Hitchcock Études', and 'Surface Tension' by Eve Egoyan and David Rokeby. This research was

Partition pour femmes et orchestre. Ethel Stark et la Symphonie féminine de Montréal - Rachwal, Maria Noriega (Éditions du remue-ménage, 2017)
En 1940, deux femmes élégantes prennent le thé dans le lobby du Ritz-Carlton. Ne vous fiez pas aux apparences: leur rencontre annonce un grand chambardement dans l’univers de la musique classique. La mécène Madge Bowen et la violoniste Ethel Stark fondent à Montréal ce qui deviendra le premier orchestre symphonique canadien composé uniquement de femmes. […]

Le son au théâtre et en danse contemporaine : les principes conceptuels récurrents de ma pratique - Tobin, Nancy (Université du Québec à Montréal, 2017)
Ce mémoire-création porte sur la conception sonore pour le théâtre et la danse contemporaine. Il vise à fournir des connaissances qui puissent faciliter l'intégration du son au sein d'une création scénique. La recherche dont il est question ici se concentre uniquement sur les aspects conceptuels et non techniques, toutes deux intrinsèques au processus de création du son. Me basant sur mon expérience de concepteure sonore, plus précisément à partir de l'étude de mes notes de chantier de création entre 1999 et 2014, je dégage dix principes récurrents qui indiquent des conditions optimales pour concevoir le son. Ce mémoire-création est l'analyse d'une approche personnelle et le processus méthodologique a été autopoïétique et heuristique. L'étude se présente en trois sections. La première s'intéresse aux récits des processus de création où chaque principe émerge à partir de l'expérience qui est racontée. Dans la deuxième section, les principes s'explicitent davantage au travers l'étude de textes sur la conception du son. Un corpus d'auteurs, surtout des praticiens de la création sonore, est déterminé pour cette partie. Un livret compose la troisième section. Il incarne la partie « création » de ce mémoire. Il s'agit encore de préciser les principes, mais cette fois au travers de dix lettres fictives, destinées à des étudiants-es. Chaque lettre, dont le sujet est un problème rencontré en cours de processus de création, vise à expliquer un principe dans un contexte concret. Le titre du livret est La conception sonore selon Nancy Tobin 01. Mon nom apparaît dans le titre pour signifier qu'il est surtout question de mon approche personnelle. La mention des chiffres « 01 » indique que le livret démarre une série où d'autres personnes conceptrices sont invitées à écrire sur leur propre expérience. Peu de textes sur la conception sonore - sur l'expérience concrète du faire - existent. Ce mémoire-création vise à combler en partie cette lacune et à inviter d'autres créateurs à écrire sur leur pratique. L'expression par le sonore est riche et diversifiée. Plus les pratiques seront partagées et diffusées, plus il sera possible de multiplier les possibles de l'espace de l'écoute.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Nicole Lizée : adepte de la hantologie - Van Vliet, Kiersten (La Scena Musicale, 2017)

Where Is She? Finding the Women in Electronic Music Culture - Abtan, Freida (Contemporary Music Review, 2016)
The author discusses the visibility and participation of women in electronic music culture. She argues that most electronic music social networks privilege male inclusion and success, and that skill-sharing is an important strategy to encourage women in the field. To seed this discussion, the author examines her own history with reflections on the gender dynamics within electronic music communities outside the academy, and the role that social and technical currencies play within them. She also discusses Ladies club, a music distribution project that led to several solo female electronic musicians taking the stage and organising events in Montreal during 2007.
Keywords: Culture; Electronic Music; Feminism; Gender; Skills-Sharing

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

Le Club musical de Québec : 125 ans - Bernier, Emmanuel (Cap-aux-Diamants, 2016)

The Songs of Violet Archer: Tracing the Evolution of One of Canada's Most Prominent Composers - Dauphinais, Paul (Université de Boston, 2016)
In this study, four sets of songs composed by Violet Archer are examined, all of which were written at different points in her career. Archer studied with Paul Hindemith in 1948 – 49, and his teachings had a tremendous impact on the young composer. The first set of songs to be analyzed, Moon Songs, was written before her time with Hindemith, and will provide a baseline from which her later, post-Hindemith, works can be compared. Following her studies with Hindemith, Archer wrote three songs, “Cradle Song,” “April Weather,” and “First Snow,” all of which show evidence of Hindemith’s influence. Her later, more mature works, Northern Landscape and Caleidoscopio Quatro, demonstrate a refined compositional technique; one in which Archer has created her own style, while maintaining aspects of the approach taught by Hindemith at Yale. This study will elaborate on the aspects of Archer’s music that evolved throughout her compositional career.
Keywords: Archer; Communication and the arts; Hindemith; Music analysis; Paul; Social sciences; Violet

Analyses of Organ Etudes Opp. 38, 66 and 72 by Rachel Laurin - Mateva, Silviya (Université d'Oklahoma, 2016)

Écritures chorégraphiques et sonores imbriquées : récits de collaborations avec Danièle Desnoyers - Tobin, Nancy (L’Annuaire théâtral : revue québécoise d’études théâtrales, 2016)
Ce texte revient sur le processus de création de trois spectacles chorégraphiques auxquels j’ai participé comme conceptrice sonore : Concerto grosso pour corps et surface métallique (1999), Duos pour corps et instruments (2003) et Là où je vis (2007). Ces parcours de recherche-création, traversés avec la chorégraphe Danièle Desnoyers (compagnie Le Carré des Lombes), permettent d’observer comment l’écriture sonore se développe in situ avec l’écriture chorégraphique. Les deux se forment ensemble en s’influençant l’une l’autre. Les trois spectacles choisis témoignent de différents modes de création de la matière sonore : amplification des danseurs, diffusion avec des haut-parleurs inusités, invention d’instruments et citation de musiques transformées. Les récits de collaborations qui suivent révèlent les manières dont la matière sonore a émergé de l’écriture chorégraphique et vice versa.

A Study of Selected Representative Organ Pieces by Rachel Laurin - Cheng, S.S. (Université du Kansas, 2015)
Over the course of the last decade the organ works of Canadian composer Rachel Laurin (b. 1961) have gained critical acclaim among professional organists. Her organ music has captured the attention of American and Canadian organists, resulting in a series of commissions for new organ works. To date, there are over thirty-two compositions for organ solo. This document explores stylistic issues in Laurin's compositions for solo organ and for organ with other instruments. Pieces that have been selected for in-depth study include Chromatic Fantasietta, Scherzetto, Toccatarina (to Katarina) and Asian Legend from Twelve Short Pieces, Volume 3, op. 64, Étude Héroïque, Op.38, and the Sonata for Organ and Horn, Op.60, II. On a Painting by Thomson. At the outset of the document an overview of Canadian organ culture is provided, followed by an introduction to Laurin's life and works. Subsequently, a structural and harmonic analysis of Laurin's compositions is presented. As this analysis will reveal, the expressive dimensions of her works embrace elements of Romanticism and Impressionism.

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (1re partie) - Henry, Symon (Circuit, 2015)

ECM+ Génération 2014 : regards sur les quatre compositeurs lauréats (2e partie) - Henry, Symon (Circuit, 2015)

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

Marketing, Merch, and Media: Nicole Lizée, in Conversation - Wiseman, Howard; Disman, Adriana (Canadian Theatre Review, 2015)
Nicole Lizée is an award-winning classical music composer and performer who composes for string quartet, electronic music, turntable, film, and other media. She has emerged as a major new voice in new classical composition, winning the coveted Canada Council for the Arts Jules Léger Prize (2013) for new Canadian chamber music with her work White Label Experiment. She has been commissioned by the Kronos Quartet among many other prestigious ensembles. This interview engages her relation to various aspects of her work, from marketing and promotion to inspiration and creation in the context of “avant garde” music. How can marketing continue to be part of the art itself? Does instinctively not fitting into a box allow for greater freedom to explore classical and chamber music in the broader context of film and other media? What other factors may be contributing to the inspired vitality of her work?
Keywords: Entretien

Glimpses Into My Compositional Style and Techniques : Text and Musical Examples - Badian, Maya (Lucian Badian Editions, 2014)

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 1 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Interviews; Music; Musical performances; Musicians & conductors; Singers

Soprano Pierrette Alarie (1921-2011), tenor Léopold Simoneau (1916-2006). Part 2 - Duffie, Bruce (Opera Journal, 2014)
Keywords: Accompanists; Composers; Librettists; Music; Musical performances; Musicians & conductors; Opera; Singers

Nicole Lizée. Faisceaux imaginaires et cool media - McKinley, Maxime (La création musicale au Québec, 2014)

Layers of creativity in composition, rehearsal and performance: Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Tracking the Creative Process in Music Second International Conference, 2013)

Le son tactile ou la sensorialité excentrique dans les performances solos de Magali Babin - Abenavoli, Lorella (Circuit : musiques contemporaines, 2013)
How can the ephemeral touch of a caress become an aesthetic object? How can a fingernail scratching the mineral surface of a sheet of schist become music? How can intimate tactile experience become the scene of a collective artistic ritual? How does Magali Babin turn electronic sound into a medium for eccentric sensoriality? This article takes us into one region of Magali Babin’s artistic practice: the tactile world of sound that she uses in her solo performances. Author of a polymorphic sonic oeuvre, Magali Babin is a Quebec artist, performer, and composer whose artistic practice has incorporated sonic installations for the past two years. She is a key figure in Montreal’s alternative audio art, “edgy” improvisation, and experimental music scenes, moving freely among cutting-edge artistic categories.
Keywords: Magali Babin; art audio; art haptique; audio art; device; dispositif; eccentric sensoriality; electronic; haptic art; improvisation; performance sonore; sensorialité excentrique; sonic performance; électronique

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

Du rôle de l'interprète-chercheur en création et re-création musicale : théories, modèles et réalisations d'après les cas de Kathinkas Gesang (1983-1984) de Karlheinz Stockhausen et de La Machi (2007-2011) d'Analía Llugdar - Breault, Marie-Hélène (Université de Montréal, 2013)
Cette thèse est basée sur une approche méthodologique hybride relevant de recherche-création en musique et de musicologie appliquée à l’interprétation. Elle s’intéresse à cette question centrale : « Quels rôles l’interprète-chercheur occupe-t-il dans un contexte de création ou de re-création (ou d’interprétation) musicale » ? Pour y répondre, l’auteure examine et rend compte du processus créateur et re-créateur de deux œuvres significatives dans son parcours en tant qu’interprète, soit Kathinkas Gesang als Luzifers Requiem (1983-1984) de Karlheinz Stockhausen et La Machi, rituel pour flûtes, électronique et regards (2007-2011) d’Analía Llugdar. Le travail de ces œuvres mixtes qui comportent toutes deux une dimension théâtrale tout en mettant en scène des personnages instrumentaux l’amène aussi à traiter des problématiques de l’appropriation de l’œuvre par l’interprète-chercheur et de la liberté de celui-ci face aux œuvres présentant un haut degré de déterminisme notationnel. La première partie situe les contextes disciplinaires et théoriques des recherches de l’auteure. Le premier chapitre permet de comprendre comment s’exerce la recherche de l’interprète en musique et de situer les différentes modalités dans lesquelles ce type de recherche s’effectue. Le deuxième chapitre explique les notions d’interprétation, d’improvisation et de composition et il situe l’interprète par rapport à ces trois champs d’activités. L’auteure y compare aussi les modes créatifs du théâtre à ceux de la musique tout en s’intéressant aux divers types d’authenticité inhérents au travail d’interprétation. Le troisième chapitre pose le principal angle d’investigation et d’analyse adopté dans cette thèse, soit celui du timbre instrumental. La deuxième partie porte sur Kathinkas Gesang de Stockhausen. Le quatrième chapitre présente une chronologie récapitulative des différentes grandes périodes d’appropriation de l’auteure. Le cinquième chapitre présente et met en contexte le symbolisme du cycle Licht, die sieben Tage der Woche (1977-2003), dans lequel Kathinkas Gesang s’insère. Le sixième chapitre est voué à une analyse du symbolisme attribué au timbre des principaux instruments que l’on retrouve dans Licht. Le septième chapitre évalue l’impact de la présence des interprètes dans le processus compositionnel chez Stockhausen tout en traitant de la question du casting dans Licht. Le huitième chapitre s’articule en un lexique timbral présentant une exégèse des techniques de jeu employées dans Kathinkas Gesang pour produire divers types de timbres. La troisième partie porte sur La Machi d’Analía Llugdar. Dans le neuvième chapitre, l’auteure présente la structure générale de l’œuvre et son synopsis et elle traite du rôle qu’elle a joué dans le processus de création de cette œuvre. Le dixième chapitre prend la forme d’un lexique timbral présentant une exégèse des différentes techniques de jeu employées dans l’œuvre pour produire divers types de timbres. Dans la conclusion, trois sphères d’action et six rôles-types de l’interprète-chercheur en création et en re-création musicale sont identifiés. De plus, des réponses aux problématiques de l’appropriation de l’œuvre et de la liberté de l’interprète sont apportées. L’auteure y suggère également des pistes de réflexion pour la recherche- création en musique et elle y présente les principales retombées de la thèse.

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Faisceaux imaginaires et cool medias : This Will Not Be Televised de Nicole Lizée - McKinley, Maxime (Circuit : musiques contemporaines, 2013)
The imagination of composer Nicole Lizée brings together disparate elements, largely drawn from cinema, philosophy, visual arts, and so-called popular music, with a pronounced penchant for the period from 1960-1980 and the ghostly effect thus conveyed. This article illustrates Lizée’s creative process through one of her characteristic works, This Will Not Be Televised (2005-2007), scored for DJ and seven instruments. Our analysis illustrates how the composer’s “beams of imagination” take form through a unique musical language, based here on a meticulously notated DJ part and extended through the instrumental ensemble, and which draws on cultural references, repetitive effects, and montages of juxtapositions and superpositions, and whose continuous form achieves cohesion through the use of repeats. In this way, the composer focuses on the connections that are generated in the memory and subjectivity of the hearer – the tabula rasa characteristic of McLuhan’s “cool” media.
Keywords: Nicole Lizée; This Will Not Be Televised; analyse; analysis; cool medias; tables tournantes; turntable; “cool” media

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

Introduction : la voix d’Ana Sokolović - Goldman, Jonathan (Circuit, 2012)

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Cartographie de l’apprentie - Messier, Anne (Circuit, 2012)
La compositrice québécoise Ana Sokolović est d’origine serbe et plusieurs de ses oeuvres font référence à son pays d’origine, que ce soit par l’utilisation de mélodies et de rythmes traditionnels ou par des références culturelles. Pour approfondir son héritage serbe, l’auteure s’est entretenue avec la compositrice en mars 2012. L’article relate les paysages de son enfance et de son adolescence, l’environnement musical, culturel et politique de ses années d’apprentissage. Le portrait de sa vie familiale et de son quotidien nous permet de saisir des éléments constituants de sa personnalité d’artiste en devenir. Sa décision de s’établir à Montréal est explorée et elle raconte comment elle a pris conscience de son héritage slave.

« J’aime quand on explose de joie ! » : entretien avec Ana Sokolović - Panneton, Isabelle (Circuit, 2012)
Lors d’un entretien réalisé par la compositrice Isabelle Panneton, Ana Sokolović discute de ses inspirations, de ses méthodes et de son rapport avec les interprètes de sa musique.

L'intuition de/dans l'œuvre de la compositrice québécoise Isabelle Panneton: un défi à la bipartition du genre - Stévance, Sophie (Le genre à l'œuvre, 2012)

Violet Archer's "The Twenty-Third Psalm" (1952): An Analytical Study of Text and Music Relations Through Fibonacci Numbers, Melodic Contour, Motives, and Piano Accompaniment - Wan, Jessica Jane (Université d'Ottawa, 2012)
This study explores text and music relations in Canadian composer Violet Archer's “The Twenty-Third Psalm” by analysing the text of Psalm 23, Fibonacci numbers, melodic contours, motives, and the role of the accompaniment. The text focuses on David's faith in God and his acceptance of God as his shepherd on earth. The four other approaches allow us to examine the work on three different structural levels: background through Fibonacci numbers, middleground through melodic contour analysis, and foreground through motivic analysis and the role of the accompaniment. The measure numbers that align with Fibonacci numbers overlap with some of the melodic contour phrases, which are demarcated by rests, as well as with the most important moments at the surface level, such as the emphasis on the word “death” through recurring and symbolic motives. The piano accompaniment further supports these moments in the text.
Keywords: Archer; Canadian music; Communication and the arts; Fibonacci numbers; Melodic contour; Motivic analysis; Music analysis; Psalm 23; Text and music relations; The Twenty-Third Psalm (1952); Theory; Violet

Entretien avec Isabelle Panneton - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2011)
Sous forme d’entrevue, la compositrice se remémore les moments importants des cours d’analyse de Gilles Tremblay, plus particulièrement sa manière d’aborder le rapport de la poésie et de la musique, ainsi que son souci du traitement vocal, une approche qui se démarque par son caractère instinctif et sa vision organique des oeuvres. La compositrice parle également de sa propre approche de la poésie et présente quelques-uns de ses projets.

La poétesse de l'ombre [entretien avec l'artiste sonore Nancy Tobin] - Siaud, Florent (Théâtre/Public, 2011)

"Give Me Aladdin's Lamp”: A Possible Perspective of Modernism - Ştefan, Angi (Musicology Papers, 2011)
Defining the differentiated semantics of new and novelty, reversing the dictum non nova sed nove into non nove sed nova, the author of the chamber cantata „Give me Aladdin’s lamp” is based on the rich experience of leading myriad of mid-century modernism. The investigation of the paradigms of new relationships between vocal and instrumental in creation of Dora Cojocaru, is directed in present at the chamber cantata for mezzo-soprano, brass quintet and percussion on lyrics by Emil & Dan Botta, Georg Trakl, Rainer Maria Rilke and Ady Endre (1998). The relations text - melody by their phenomenological reduction to fruitful combinations between poetic word - musical sound in Dora Cojocaru’s cantatas represent a stylistic-rhetorical subsumption of autochthonous and foreign experiences in promoting new compositional and interpretive skills meant for adaptation of appropriate musical expression in portraying contemporary aesthetic message. They are designed on the wide range of contemporary aesthetic values from the grotesque in nascendi to the absurd in morendi. As long as the Cantata Galgenlieder in der Nacht with lyrics by Christian Morgenstern (1995) is conceived at the grotesquely pole on the axis of the field of contemporary aesthetics, the Cantata Give me Aladdin’s lamp is designed in the sphere of the tragic. In the composer’s vocal and instrumental creation (and not only in them) the experiences of today’s musical composition and interpretation are rethought creatively, suggesting in perspective the permanence of modern horizons.

Le 'principe de contrainte stimulante' dans l'œuvre de la compositrice Isabelle Panneton - Stévance, Sophie (Médecine des arts, 2011)

Être compositeur aujourd'hui : entretien de Sophie Stévance avec Isabelle Panneton - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Quelle place pour les femmes dans la création musicale au XXIe siècle ? - Stévance, Sophie (Composer au XXIe siècle. Pratiques, philosophies, langages et analyses, 2010)

Reprise et intertextualité musicale. L’hommage à La Bolduc par des compositrices engagées vers l’avant - Stévance, Sophie (Volume ! La revue des musiques populaires, 2010)
Cet article étudie la notion de reprise sous l’angle de l’Hommage à La Bolduc rendu par sept compositrices à Mary Travers (alias La Bolduc), icône de la musique populaire au Québec dans les années 1930, à l’occasion du Festival SuperMicMac. Par des allusions, des références précises et explicites ou par de simples emprunts et citations, ces hommages sont autant de lectures que de relectures des chansons sélectionnées en abordant différents modes de jeux d’«  intertextualité musicale  ». Celle-ci se situe à deux niveaux  : le pôle de la production, qui montre que les chansons engagées de La Bolduc sont elles-mêmes le témoignage d’une époque  ; le pôle de la réception, pour exposer les résonances de ces chansons à partir de références autres et communes à la fois, comme la place des femmes dans la création musicale. Cette étude envisage ainsi la reprise à partir des aspects, des significations et des enjeux musicaux posés par l’intertextualité musicale, ici abordée sous l’angle de l’hommage alors conçu comme «  réactivateur  » de sens.
Keywords: concert / live / festival; féminité / masculinité / genre; intertextualité (musicale); politique / militantisme; reprise / pastiche / parodie; réception